Soft pneumatic artificial muscle (PAM) robotic ARM [electronic resource] - Ting, Kie Seng, 1989-, author (2013)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2013